Gamified Telerehabilitation in Oligoarticular Juvenile Idiopathic Arthritis: A Randomized Controlled, Single‐Blind Trial - Leblebici, Gokce; Kısa, Eylul Pinar; Tarakci, Ela; Gunhan, Iremnur; Yenici, Emine Nur; Kasapcopur, Ozgur (International journal of rheumatic diseases, 2025)
ABSTRACT Introduction This study aimed to investigate the effect of the 6‐week gamified exercise program, delivered via telerehabilitation, on pain, kinesiophobia, quality of life, and mobility in children with oligoarticular juvenile arthritis (JIA). Methods Forty children with oligoarticular JIA (mean age: 11.86 ± 3.79 years) were randomly divided into two groups: Group I received game‐based exercises via a telerehabilitation protocol, while Group II followed a home exercise program. The Wong Baker Pain Scale, Tampa Kinesiophobia Scale (TKS) and Pediatric Quality of Life Inventory (PedsQL) 3.0 Arthritis Module were completed by the patients. Patients' joint range of motion (ROM) and walking speed were measured by a blinded physiotherapist. The gamified exercises in the telerehabilitation program were supervised by another physiotherapist via WhatsApp video calls three times a week. Additionally, the exercise program was scheduled in the patients' calendars using Google Fit to provide reminders. Results There was a significant improvement in the ROM, walking speed, pain, kinesiophobia, and quality of life in the telerehabilitation group (p < 0.05). After the intervention, the telerehabilitation group showed greater improvements compared to the control group in hip and ankle ROM values, walking speed, and quality of life scores for ages 13–18 (p < 0.05). Conclusion The 6‐week gamified telerehabilitation program reduced pain symptoms and kinesiophobia behaviors while improving the participants' quality of life and mobility. Trial Registration ClinicalTrials.gov NCT05837247